Diagnostic and morphometric studies on dilated cardiomyopathy in mixed breed cats - R. T. Reem; H. Abdel-Saeed; M. E. Ali; A. F. El Karmoty (Bulgarian Journal of Veterinary Medicine)
Feline dilated cardiomyopathy (DCM) is a rare condition, with idiopathic etiology, non-specific clini-cal manifestations, and sudden death. The DCM diagnostic protocol was studied in mixed-breed cats along with the morphometric study of their hearts. Sixteen mixed-breed cats were examined for diag-nostic studies and six mixed-breed cats have been studied anatomically. DCM cats had severe respira-tory distress and abdominal distention. The physical examinations revealed an increase in respiration rate of 89±5.90 min–1 and pulse rate of 166±5.25 min–1. The diagnosis protocol revealed abnormal darker dots in IDEXX SNAP Feline pro-BNP test. Macro-anatomically, the DCM heart was large, ovoid in shape with a rounded apex, the interventricular septum thickness was significantly decreased to 2.9±0.03 mm, and the left ventricular lumen of DCM was significantly increased to 27.2±0.39 mm. Morphometrically, the whole size of the DCM heart was 43.1±0.03 mm. Radiographic examinations showed marked pleural effusion and abnormal enlargement of the heart. In echocardiography DCM cats showed a significant increase in heart rate, left ventricle internal diameter in diastole (LVIDd), interventricular septum systole (IVSs), left ventricle internal diameter in systole (LVIDs), and left atrium to aortic diameter ratio (LA/AO). The colour Doppler echocardiography showed turbulence in mitral, tricuspid, and aortic valve regurgitation. Pulsed and continuous wave Doppler echocardiography revealed a disparity in the flow velocity associated with valve regurgitation. Respiratory distress in cats should be investigated for the presence of cardiac diseases.